THE EFFECT OF SCANNING TECHNIQUE ON STUDENTS’ ADVERTISEMENT TEXT COMPREHENSION - Pratiwi, Asty Eka; Rafiqa, Syarifa; Indra, Indra (Borneo Journal of English Language Education, 2024)
This research aims to prove whether the scanning technique is effective in teaching reading comprehension to students. This research used a pre-experimental research design and took one class, 9.1, as the sample. The analysis showed that the scanning technique greatly contributed to students' comprehension of reading advertisement texts. This can be seen from the increase in students' scores in the pre-test and post-test. The average score in the pre-test was 58.52 and increased to 74.07 in the post-test. Then, the data from both tests were analyzed using the significance parameter, and the results showed that the sig. (2-tailed) was 0.00, which means the sig. value (2-tailed) 0.05. Following the testing criteria, the results showed a significant increase in students' achievement in reading comprehension by using the scanning technique before and after the pre-test and post-test were conducted. This means that the scanning technique is effective and can be applied in grade nine of SMP Negeri 9 Tarakan to teach students reading comprehension.